2015
DOI: 10.1007/s00894-015-2751-9
|View full text |Cite
|
Sign up to set email alerts
|

Topological insights into the 1/1 diacetyl/water complex gained using a new methodological approach

Abstract: The 1/1 diacetyl/water complex is of atmospheric relevance. Previous experimental and theoretical studies have focused on two isomeric forms, and geometry optimizations were carried out on them. Herein, we propose a six-step methodological approach based on topological properties to search for and characterize all of the isomeric forms of the 1/1 noncovalent diacetyl/water complex: (1) a molecular electrostatic potential (MESP) study to get an overview of the V min and V max regions on the molecular surfaces o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…In a recent theoretical paper about 1/1 DAC/H 2 O complex 12 we have shown that the analysis of monomers realized with the combination of topological tools, mainly MESP, ELF and QTAIM allowed identifying favorable interaction sites to predict 1/1 structures. Three isomers have been characterized, namely S 1 , S 2 and S 3 , and their structures optimized at the MP2/AVTZ level of theory are reported in Figure 1.…”
Section: Iii-1 Theoretical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent theoretical paper about 1/1 DAC/H 2 O complex 12 we have shown that the analysis of monomers realized with the combination of topological tools, mainly MESP, ELF and QTAIM allowed identifying favorable interaction sites to predict 1/1 structures. Three isomers have been characterized, namely S 1 , S 2 and S 3 , and their structures optimized at the MP2/AVTZ level of theory are reported in Figure 1.…”
Section: Iii-1 Theoretical Resultsmentioning
confidence: 99%
“…It has been shown in many previous solid 8 and gas phase studies [9][10][11] that very different structural architectures of hydrated organic 2 M/H 2 O clusters could be obtained, depending on the nature of the organic molecule M involved. The objective of the present work is to characterize by a combined experimental and theoretical approach the first step of hydration of an organic molecule M. In a recent paper 12 , a six-step methodological approach aiming at characterizing the conformational landscape of mono-hydrated 1/1 M/H 2 O isomers emphasized the value of topological methods to evidence the most stable isomers. We selected the small centro-symmetric diacetyl molecule (C 4 H 6 O 2 , DAC) as partner of the hydration process.…”
Section: -Introductionmentioning
confidence: 99%
“…The MESP is found to be a powerful tool for studying molecular surfaces . In this study, the MESP calculations demonstrated the negative potential at cyclopropane bonds which is responsible for the interaction with electropositive Li + ions.…”
Section: Resultsmentioning
confidence: 63%
“…The MESP is found to be a powerful tool for studying molecular surfaces. [58][59][60] In this study, the MESP calculations demonstrated the negative potential at cyclopropane bonds which is responsible for the interaction with electropositive Li + ions. The change in V min values upon addition of each Li + ion indicates the depletion of electron density on other cyclopropane bonds.…”
Section: Molecular Electrostatic Potential Study (Mesp)mentioning
confidence: 57%
“…Additionally, this well-established tool is efficient in understanding various chemical properties like chemical reactivity, intermolecular interactions and inductive effects, etc. (Dargent et al, 2015). The most negative (V min , red region) and positive (V max , blue region) electrostatic potential value in MESP indicate the electron donating and accepting tendency in a particular molecule, respectively (Matta, 2014).…”
Section: Molecular Electrostatic Potential Surfacementioning
confidence: 99%